Enhancing gross motor skills through tari piring: a classroom action research in early childhood education - Heny Wulandari; Jihan Karenita Sari (CV. SPDFHarmony, 2025)
Background: Gross motor development is a crucial component of early childhood education, as it supports children’s balance, coordination, and overall physical readiness for learning. In practice, gross motor stimulation often relies on repetitive physical exercises that may not fully engage children. Movement-based arts, particularly traditional dance, offer an alternative learning approach that integrates physical activity, rhythm, cultural meaning, and emotional engagement. However, empirical studies examining traditional dance as a structured learning strategy for gross motor development in early childhood classrooms remain limited. Aims: This study aims to enhance the gross motor skills of early childhood learners through the implementation of the Traditional Plate Dance (Tari Piring) using a classroom action research approach. Method: This study employed Classroom Action Research based on the Kemmis and McTaggart model, conducted in two cycles. The participants were 10 children aged 5–6 years enrolled at PAUD Kartini Jatimulyo, South Lampung. Data were collected through observation, interviews, and documentation, and analyzed using a combination of quantitative developmental achievement analysis and qualitative descriptive interpretation. Results: The findings demonstrate a substantial improvement in children’s gross motor skills across research cycles. The proportion of children categorized as Very Well Developed increased from 40 percent in Cycle I to 80 percent in Cycle II, while no children remained in the not yet developed category. Children showed improved balance, coordination, rhythmic movement, and active participation during dance activities. Conclusion: The implementation of Tari Piring as a movement-based learning strategy effectively improves gross motor skills in early childhood education. Traditional dance provides meaningful, engaging, and culturally contextualized learning experiences that support children’s physical development.